(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
This paper describes two contemporary houses and their respective gardens: the small post-earthquake temporary shelters in Onna, Italy and Derek Jarman’s Prospect Cottage in Southern England. To dwell, as per the Heideggerian perspective, is an act of cultivation of the soil, the transformation of wilderness into a tilled (architectural) garden: it entails rootedness, permanence, and recurring practices of care. Nevertheless, what these two architectural gardens show is that in our time, while caring for the land can still epitomize the subjugation of chthonic forces, attempting to institute an ecological relation of domination, it may also point in an altogether different direction. In Onna, the gardens appear as an act of resistance against the menacing forces of wilderness; Jarman’s attitude is that of a pathic acceptation of the atmospheric powers pervading the vast marine environment.